2011
DOI: 10.1074/jbc.m110.151548
|View full text |Cite|
|
Sign up to set email alerts
|

Pigment Epithelium-derived Factor and Its Phosphomimetic Mutant Induce JNK-dependent Apoptosis and p38-mediated Migration Arrest

Abstract: Pigment epithelium-derived factor (PEDF) is a potent endogenous inhibitor of angiogenesis and a promising anticancer agent. We have previously shown that PEDF can be phosphorylated and that distinct phosphorylations differentially regulate its physiological functions. We also demonstrated that triple phosphomimetic mutant (EEE-PEDF), has significantly increased antiangiogenic activity and is much more efficient than WT-PEDF in inhibiting neovascularization and tumor growth. The enhanced antiangiogenic effect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
(65 reference statements)
1
23
0
Order By: Relevance
“…The exciting observation was that PEDF also exhibits its known survival effect on the neurons that shielded the brain from tumour-induced damage. In culture, PEDF exhibits potent antimigratory activity on human breast tumour cells 77,78 and neuroprotectant activity on neurons. These observations emphasize the dual role of PEDF as both a metastatic suppressor and a neuroprotectant in the brain.…”
Section: Pedf and Its Relevance To Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…The exciting observation was that PEDF also exhibits its known survival effect on the neurons that shielded the brain from tumour-induced damage. In culture, PEDF exhibits potent antimigratory activity on human breast tumour cells 77,78 and neuroprotectant activity on neurons. These observations emphasize the dual role of PEDF as both a metastatic suppressor and a neuroprotectant in the brain.…”
Section: Pedf and Its Relevance To Cancermentioning
confidence: 99%
“…They also showed that PEDF upregulated presenilin 1, which facilitates the association between protein tyrosine phosphatases and VEGFR1 to inhibit VEGF-induced phosphorylation of VEGFR1. Konson and co-workers 77 reported that different tumour-suppressive activities of PEDF are independently regulated by two different MAPK pathways: the JUN N-terminal kinase (JNK) pathway regulates the endothelial pro-apoptotic activity and the p38 MAPK pathway regulates antimigratory activities. The contributions of the Volpert laboratory elucidated how PEDF regulates CD95 ligand (CD95L; also known as FAS ligand) and cellular FLICE-like inhibitory protein (FLIP) to inhibit neovascularization in activated endothelial cells 66,88 .…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%
See 3 more Smart Citations